1998
DOI: 10.1097/00002820-199804000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of fatigue in survivors of breast cancer

Abstract: The purpose of this report is to describe variables associated with fatigue for disease-free survivors of breast cancer. On the basis of Mishel's theory of illness uncertainty and the antecedents of uncertainty, a cross-sectional, descriptive, correlational design was used to examine (a) the relationship of fatigue with cancer-related variables and the presence of concurrent illness and (b) whether fatigue and educational level explained a significant proportion of the variation in illness uncertainty. The Mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
8

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 24 publications
2
47
1
8
Order By: Relevance
“…However, in a recent study fatigue has been shown to be associated with sleep quality but not with sleep latency [19]. An association between fatigue and the severity of pain has been confirmed in several research studies [8,21,27,30]. The contribution of pain to fatigue in cancer patients might be explained in several ways.…”
Section: Discussionmentioning
confidence: 94%
“…However, in a recent study fatigue has been shown to be associated with sleep quality but not with sleep latency [19]. An association between fatigue and the severity of pain has been confirmed in several research studies [8,21,27,30]. The contribution of pain to fatigue in cancer patients might be explained in several ways.…”
Section: Discussionmentioning
confidence: 94%
“…Earlier studies on possible mechanisms have found no consistent association between fatigue and stage of disease, extent of treatment, time since treatment completion, type of surgery or use of tamoxifen. 5,7,8 Some studies have investigated the role of the immune system and, in particular, the role of cytokines in relation to fatigue in breast cancer survivors. [9][10][11][12][13][14][15] Fatigued breast cancer survivors have been shown to have significantly higher levels of proinflammatory cytokines and circulating T lymphocytes compared with non-fatigued survivors.…”
Section: Introductionmentioning
confidence: 99%
“…192,203 Emerging evidence suggests that fatigue persists even after acute treatment is completed, 214 and correlates with the use of chemotherapy, irrespective of the time since treatment. 215 …”
Section: Fatiguementioning
confidence: 99%